UPAYA PENGEMBANGAN TARI IYO-IYO DI SD NEGERI NOMOR 15/III DESA TANJUNG PAUH MUDIK KECAMATAN KELILING DANAU KABUPATEN KERINCI - Tia Ivontia Vita; Darmawati Darmawati; Susmiarti Susmiarti (SENDRATASIK UNP, 2014)
Abstract The article aims at exploring the developing of Iyo-Iyo dance in SD Negeri 15/III Tanjung Pauh Mudik, Keliling Danau, Kerinci. This was a descriptif qualitative study. The technique of data collection used were literature study, observation, interview, and documentation. The data analisis was done trough classifying the data based on the concept frame. The result indicated that the effort to attain the development of Iyo-Iyo dance in SD 15/III Kerinci was done throught teaching the dance to the students which are not the offspring of “ depati anum “ who also regards as the Iyo-Iyo dancer in “ kenduri sko “ event. The training of Iyo-Iyo dance was conducted during juli 2-6 2013. The Iyo-Iyo dance taught to the students was only introduced as an ordinary and entertaining dance to audience, not as a costom and ritual dance.   Kata kunci: Upaya, Pengembangan, tari, Iyo-Iyo